A Comprehensive Analysis of the Lysine Acetylome in the Aquatic Animals Pathogenic Bacterium Vibrio mimicus - Wang, Junlin; Pang, Huanying; Yin, Linlin; Zeng, Fuyuan; Wang, Na; Hoare, Rowena; Monaghan, Sean J.; Li, Wanxin; Jian, Jichang (Frontiers in Microbiology, 2022)
Protein lysine acetylation is an evolutionarily conserved post-translational modification (PTM), which is dynamic and reversible, playing a crucial regulatory role in almost every aspect of metabolism, of both eukaryotes and prokaryotes. Several global lysine acetylome studies have been carried out in various bacteria, but thus far, there have been no reports of lysine acetylation for the commercially important aquatic animal pathogen Vibrio mimicus. In the present study, we used anti-Ac-K antibody beads to highly sensitive immune-affinity purification and combined high-resolution LC-MS/MS to perform the first global lysine acetylome analysis in V. mimicus, leading to the identification of 1,097 lysine-acetylated sites on 582 proteins, and more than half (58.4%) of the acetylated proteins had only one site. The analysis of acetylated modified peptide motifs revealed six significantly enriched motifs, namely, KacL, KacR, L(-2) KacL, LKacK, L(-7) EKac, and IEKac. In addition, bioinformatic assessments state clearly that acetylated proteins have a hand in many important biological processes in V. mimicus, such as purine metabolism, ribosome, pyruvate metabolism, glycolysis/gluconeogenesis, the TCA cycle, and so on. Moreover, 13 acetylated proteins were related to the virulence of V. mimicus. To sum up, this is a comprehensive analysis whole situation protein lysine acetylome in V. mimicus and provides an important foundation for in-depth study of the biological function of lysine acetylation in V. mimicus.